Effect of surface preparation by high-temperature hydrogen annealing on the passivation of Ni-20 at.% Cr alloy in sulfuric acid. (20th June 2023) - Han, Junsoo; Neupane, Shova; Wang, Luntao; Seyeux, Antoine; Klein, Lorena; Zanna, Sandrine; Mercier, Dimitri; Maurice, Vincent; Marcus, Philippe
Highlights: Investigation of native and passive surface films formed on Ni-20 at.% Cr alloy surfaces. Surface analysis by in situ electrochemical measurements combined with advanced ex situ surface analysis. Mechanistic understanding of the effects of high-temperature hydrogen annealing pretreatment. Enhanced corrosion resistance of electrochemically passivated surface by high-temperature hydrogen annealing pretreatment. Increase in Cr enrichment of initially weakly protected sites of the inner barrier layer. Abstract: The effect of high-temperature annealing under hydrogen gas (H2 ) surface preparation on a binary polycrystalline Ni-20 at.% Cr alloy was investigated in comparison with conventional mechanical grinding surface preparation. Duplex surface films with inner Cr(III) oxide and outer Ni(II) and Cr(III) hydroxide layers natively formed before and after H2 annealing were characterized by X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectroscopy. A thinner and less homogeneous inner barrier layer formed after H2 annealing caused an oxidation peak at the active/passive transition in the linear sweep voltammetry measurement in a 0.5 M H2 SO4 solution. Despite this high oxidation peak, passivation of the H2 annealed surface resulted in the formation of a more corrosion resistant inner layer than on the mechanically ground surface, as demonstrated by electrochemical impedance spectroscopy. The corrosion resistant passive film formation of the H2 annealed surface is attributed to the increased Cr enrichment of the inner layer caused by the selective Ni dissolution providing corrosion resistance to the initially weakly protected sites of the natively formed surface film.